2000
DOI: 10.1046/j.1523-1747.2000.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Augment the Chemically Induced Production and Gene Expression of Interleukin-1α through NF-κB and AP-1 Activation in Murine Epidermal Cells

Abstract: To clarify the mechanism of the glucocorticoid-induced augmentation of skin response, we attempted to demonstrate the modulatory effect of glucocorticoids on the regulation of cytokines produced by keratinocytes stimulated with various chemicals in vitro. Haptens, irritants, and a superantigen (staphylococcal enterotoxin B) induced a significant release of interleukin-1alpha and tumor necrosis factor alpha, but not interleukin-10, from a murine keratinocyte cell line, Pam 212 cells. Glucocorticoids (10(-6)-10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 25 publications
5
23
0
Order By: Relevance
“…It has also been demonstrated that glucocorticoids (0.1-1000 nM) by themselves could augment the production of IL-1a by PAM 212 cells (murine epithelial cell line) at both the protein and mRNA levels after 6 h of coincubation. When these cells were stimulated for 24 h with haptens or irritants, which alone increased the IL-1a production, glucocorticoids synergistically enhanced the effect [27,28]. NF-nB activation was also revealed in parallel with these observations; nevertheless, Lukiw et al showed inhibition of DNA binding of NF-nB by 100 nM budesonide epimer R and dexamethasone in keratinocytes activated by IL-1h or platelet-activating factor (PAF) [15].…”
Section: Discussionsupporting
confidence: 91%
“…It has also been demonstrated that glucocorticoids (0.1-1000 nM) by themselves could augment the production of IL-1a by PAM 212 cells (murine epithelial cell line) at both the protein and mRNA levels after 6 h of coincubation. When these cells were stimulated for 24 h with haptens or irritants, which alone increased the IL-1a production, glucocorticoids synergistically enhanced the effect [27,28]. NF-nB activation was also revealed in parallel with these observations; nevertheless, Lukiw et al showed inhibition of DNA binding of NF-nB by 100 nM budesonide epimer R and dexamethasone in keratinocytes activated by IL-1h or platelet-activating factor (PAF) [15].…”
Section: Discussionsupporting
confidence: 91%
“…The present results clearly demonstrate IL-1 ␣ production of human normal KCs to differ from that of the murine KC cell line Pam in which IL-1 ␣ , following various stimuli, is secreted into the supernatant [4] . But in normal human newborn KCs, it is not secreted into the supernatant but stored in their cytosols.…”
Section: Discussionmentioning
confidence: 99%
“…Human newborn KCs were cultured with 0.1 m M TNBS (Wako Pure Chemicals Ltd., Osaka, Japan) and in the presence or absence of 10 -6 to 10 -14 M hydrocortisone (Banyu Pharmaceutical Co., Tokyo, Japan), 10 -6 to 10 -14 FK506 (Fujisawa Pharmaceutical Co., Tokyo, Japan), and further application of FK506 to TNBS-treated KCs with 10 -10 M hydrocortisone [4] (and see the results), in KBM (without growth factor supplements) for 24 h in a CO 2 incubator at 37 ° C.…”
Section: Agentsmentioning
confidence: 99%
See 2 more Smart Citations